2017
DOI: 10.18632/oncotarget.18516
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the association between three microRNA polymorphisms and breast cancer susceptibility

Abstract: Single nucleotide polymorphisms (SNPs) in three microRNAs (miRNAs), rs2910164 in miR-146a, rs11614913 in miR-196a2, and rs3746444 in miR-499, have been associated with breast cancer (BC) susceptibility, but the evidence is conflicting. To obtain a more robust assessment of the association between these miRNA variants and BC risk, we carried out a meta-analysis through systematic literature retrieval from the PubMed and Embase databases. A total of 9 case-control studies on rs2910164, 12 on rs11614913, and 7 on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…Therefore, the association of MIR499A rs3746444 polymorphism with breast cancer susceptibility among non-Asian populations remained unclear. Nevertheless, a major strength of the present work is that it included a larger number of studies and subjects compared to previous reports on this topic 45,46 . Thus, the present meta-analysis provided an updated and integrated estimate of the association between the polymorphism and breast cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the association of MIR499A rs3746444 polymorphism with breast cancer susceptibility among non-Asian populations remained unclear. Nevertheless, a major strength of the present work is that it included a larger number of studies and subjects compared to previous reports on this topic 45,46 . Thus, the present meta-analysis provided an updated and integrated estimate of the association between the polymorphism and breast cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…The human miR-146a gene at locus 5q34 has been linked with BRCA1/BRCA2 activity. The SNP rs2910164:G>C, located in the middle of the miRNA stem hairpin, leads to a change from a G:U pair to a C:U mismatch in the stem structure of the precursor molecule, altering the expression of mature miR-146a [ 44 ]. This SNP has been associated with the risk of various cancers [ 45 , 46 ], and with cancer-specific and ethnicity-dependent effects [ 23 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…The variant rs3746444 in the mature miR-499-3p produces a change from an A:U pair to a G:U mismatch in the stem structure of the precursor molecule, leading to an altered processing and expression of the mature transcript [ 44 ], and potentially affecting the binding of the target mRNAs to the mature miRNA-3p [ 44 ]. miR-499 can target regulation of FOXO4 , PDCD4 , Sox6 , and Rod1 expression [ 47 , 48 , 49 ], all of which play important roles in the etiology of various cancers [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also evidencing the differences of the effect of rs2910164 on the risk of BC in diverse populations, the allele rs2910164G was associated with increased risk of sporadic BC in Australians (OR =1.77, p < 10 -4 ; Uphadhyaya et al, 2015) and Iranians (OR = 1.91, p = 0.03; Barjui et al, 2017). Other studies, on the other hand, reported no association (Zhang et al, 2016;Mu et al, 2017).…”
Section: Discussionmentioning
confidence: 89%
“…The association of rs2910164 and BC was studied in several studies from different populations (Xu et al, 2013;Dai et al, 2015;Uphadhyaya et al, 2015;Barjui et al, 2017;Zhang et al, 2017). Dai et al (2015) showed that the effect of rs2910164 on BC susceptibility is different across populations.…”
Section: Discussionmentioning
confidence: 99%